2014
DOI: 10.1177/0956462414561034
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury among HIV-infected patients admitted to the intensive care unit

Abstract: We describe the incidence, associations and outcomes of acute kidney injury (AKI) among HIV-infected patients admitted to the intensive care unit (ICU). We retrospectively analysed 223 admissions to an inner-London, University-affiliated ICU between 1999 and 2012, and identified those with AKI and performed multivariate analysis to determine associations with AKI. Of all admissions, 66% were affected by AKI of any severity and 35% developed stage 3 AKI. In multivariate analysis, AKI was associated with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
2
17
0
2
Order By: Relevance
“…However, in a study by Randall et al . , despite the association of previous AIDS‐defining conditions and AKI risk, it was found that CD4 count, HIV viral load and antiretroviral medication exposure were not associated with AKI risk.…”
Section: Risk Factorsmentioning
confidence: 74%
See 2 more Smart Citations
“…However, in a study by Randall et al . , despite the association of previous AIDS‐defining conditions and AKI risk, it was found that CD4 count, HIV viral load and antiretroviral medication exposure were not associated with AKI risk.…”
Section: Risk Factorsmentioning
confidence: 74%
“…The severity of acute illness as quantified by the SAPS II or APACHE II scores has also been associated with AKI in studies by Lopes et al and Randall et al [35,36]. The presence of sepsis is also a predictor of AKI in HIVinfected patients [25,26,29].…”
Section: Hiv-independent Risk Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…The highest AKI incidence, as expected, was observed in intensive care unit settings, ranging from 47 to 66%. The main risk factors were previous comorbidities such as CKD and illness severity [27, 28]. …”
Section: Introductionmentioning
confidence: 99%
“…In different settings nephrotoxicity accounted for up to 30% of AKI episodes [28]. Medications frequently used to treat HIV-related infections have been associated with AKI, such as aminoglycosides, pentamidine, amphotericin and trimethoprim/sulfamethoxazole, and antivirals such as acyclovir and foscarnet, among others.…”
Section: Introductionmentioning
confidence: 99%